Pelayanan BPJS Peserta pada Jaminan Kesehatan di BPJS Kesehatan Kantor Padang Lawas Utara - Siregar, Jumriani; Daulay, Aqwa Naser (IAI Nasional Laa Roiba Bogor, 2024)
Quality health services are a right for every individual, including participants of the Health Social Security Administering Agency (BPJS). This study aims to analyze the services provided to BPJS Health participants in the North Padang Lawas area, with a focus on North Padang Lawas Health BPJS. The research method used is a descriptive approach with qualitative methods, direct observation, interviews with participants and officers, as well as analysis of secondary data related to service performance. The research results show that although BPJS Health has provided wider access to health services for the community, there are several challenges faced by participants in the North Padang Lawas area. Some of these are limited health facilities, especially in rural areas, long waiting times to receive services, and sometimes inadequate availability of medicines. The quality of service is also a major concern, where there are complaints regarding the attitude and responsiveness of officers and the availability of adequate medical personnel. In this context, increasing training for officers and improving health infrastructure in this region are very necessary to improve services to BPJS Health participants. This research contributes to the understanding of the quality of health services in the North Padang Lawas area, as well as providing a basis for BPJS Health and local governments to make necessary improvements to increase the quality and accessibility of health services for the community.